Comparative mRNA and MicroRNA Profiling during Acute Myocardial Infarction Induced by Coronary Occlusion and Ablation Radio-Frequency Currents - Santana, Eduardo T.; Feliciano, Regiane dos Santos; Serra, Andrey J.; Brigidio, Eduardo; Antonio, Ednei L.; Tucci, Paulo J. F.; Nathanson, Lubov; Morris, Mariana; Silva, José A. (Frontiers in Physiology, 2016)
The ligation of the left anterior descending coronary artery is the most commonly used experimental model to induce myocardial infarction (MI) in rodents. A high mortality in the acute phase and the heterogeneity of the size of the MI obtained are drawbacks recognized in this model. In an attempt to solve the problem, our group recently developed a new MI experimental model which is based on application of myocardial ablation radio-frequency currents (AB-RF) that yielded MI with homogeneous sizes and significantly reduce acute mortality. In addition, cardiac structural and functional changes aroused by AB-RF were similar to those seen in animals with MI induced by coronary artery ligation. Herein, we “compared mRNA expression of genes that govern post-MI milieu in occlusion and ablation models.” We analyzed 48 mRNAs expressions of 9 different signal transduction pathways (cell survival and metabolism signs, matrix extracellular, cell cycle, oxidative stress, apoptosis, calcium signaling, hypertrophy markers, angiogenesis and inflammation) in rat left ventricle 1 week after MI ‘”generated” by “both” coronary occlusion and AB-RF. Furthermore, high-throughput miRNA analysis was also assessed “in both” MI procedures. Interestingly, mRNA expression levels and miRNA expressions “showed strong similarities between both models after MI, with few specificities in each model, activating similar signal transduction pathways. To our knowledge, this is the first comparison of genomic alterations of” mRNA and miRNA contents after two different MI procedures and identifies key signaling regulators modulating the pathophysiology of these two models that might culminate in heart failure. Furthermore, these analyses “may contribute with the current knowledge concerning transcriptional and post-transcriptional changes of AB-RF protocol, arising as an alternative and effective MI method that reproduces most changes seem in coronary occlusion.”